America : a narrative history single-volume - Tindall, George Brown; Shi, David ([S.l.] : W W Norton & Co Inc (Np), 2003)
With nearly a million copies sold over five editions, America: A Narrative History is distinguished by its clear, colorful narrative and balanced incorporation of political history with social, cultural, and economic events. Retaining these classic strengths, the Sixth Edition introduces a new theme$1 (Bthe role of work in American life$1 (Band explores its social, political, and cultural dimensions. With an updated ancillary package that includes the new Norton Map Workbook in American History, America remains a superb choice for the US history survs